PERTUMBUHAN DAN HASIL JAGUNG MANIS PADA BERBAGAI WAKTU APLIKASI BOKASHI LIMBAH KULIT BUAH KAKAO DAN PUPUK ANORGANIK - Nurhayati Nurhayati (Agroland: Jurnal Ilmu-ilmu Pertanian, 2006)
This experiment was intended to study effects application time of bokashi cocoa pod husk and dosage of inorganic fertilizer mixture on the growth and yield of sweet corn.  The experiment employed a factorial randomized block design with two factors. The first factor was two levels of the bokashi application time: two or one week before planting time. The second factor was three dosages of organic fertilizer:  133.3 kg/ha of urea + 100 kg/ha of SP-36 + 83.3 kg/ha of KCL, 266.6 kg/ha of urea + 200 kg/ha of SP-36 + 166.6 kg/ha of KCl, and 400 kg/ha of urea + 300 kg/ha of SP-36 + 250 kg/ha of KCl. Data were analyzed with honestly significant difference (HSD) at 5 % significant level. Results showed there was no interaction between the two factors in affecting the parameters observed. It showed that time application of bokashi cocoa pod husk significantly affected the length of corn cob, while the inorganic fertilizer significantly affected the weight of corn cob. Results of the HSD test indicated that the best corn cob length (22.96 cm) was obtained for one week bokashi application prior to planting with inorganic fertilizer of  400 kg/ha of urea + 300 kg/ha of SP-36 + 250 kg/ha of KCl.